Associations of ANGPTL proteins and complexes with progression of coronary artery calcification and coronary events - Silbernagel, Günther; Higbie, Halle; Meininger, Tanja; Lemen, Deven; Li, Hongxia; Chen, Yan Q.; Wen, Yi; Zhen, Eugene Y.; Qian, Yue-Wei; Korovianskaia, Polina; Trampisch, Hans J.; Scharnagl, Hubert; et al. (Atherosclerosis, 2025)
Background and aims - Angiopoietin-like protein 8 (ANGPTL8) forms complexes with ANGPTL3 and ANGPTL4 to regulate lipoprotein lipase (LPL) activity, and decreased LPL activity is an established cardiovascular risk factor. Serum levels of ANGPTL4/8 and C-terminal domain-containing ANGPTL4 (CD-ANGPTL4) are positively associated with cardiovascular death, however, the underlying mechanisms remain incompletely understood. The present study investigated relationships of ANGPTL3, ANGPTL3/8, CD-ANGPTL4, and ANGPTL4/8 with coronary artery calcification (CAC) progression (using Agatston scores) and incident coronary events. - Methods - ANGPTL3, ANGPTL3/8, CD-ANGPTL4, and ANGPTL4/8, were measured using dedicated immunoassays in participants of the Heinz Nixdorf Recall (HNR) study, an unselected, population-based cohort of subjects free from cardiovascular disease at baseline. CAC measurements were performed at baseline and after 5 years in 2887 participants, and there was follow-up for coronary events (median duration 18.8 years). - Results - Median Agatston scores increased over 5 years from 6.70 (t0) to 24.75 (t1), and 315 participants experienced a coronary event. Concentrations of ANGPTL3 and ANGPTL3/8 were not associated with Agatston score progression. ANGPTL3 was associated with incident coronary events, whereas ANGPTL3/8 was not. In contrast, CD-ANGPTL4 and ANGPTL4/8 were positively associated with both Agatston score progression and incident coronary events. - Conclusions - Associations of ANGPTL3 and ANGPTL3/8 with coronary atherosclerosis progression and incident coronary events were inconsistent, while CD-ANGPTL4 and ANGPTL4/8 were associated with both coronary atherosclerosis progression and incident coronary events. Associations of ANGPTL4/8 and CD-ANGPTL4 with cardiovascular events may reflect progression of coronary atherosclerosis conferred by diabetes, inflammation, or the potential intrinsic effects of CD-ANGPTL4 and ANGPTL4/8.